2022
DOI: 10.1029/2021jf006367
|View full text |Cite
|
Sign up to set email alerts
|

Floods on Alluvial Fans: Implications for Reworking Rates, Morphology and Fan Hazards

Abstract: Flood events drive change on alluvial fans. Although geomorphic change is not negligible in the intervening low or moderate flows (i.e., "secondary processes"; Blair and McPherson (1994b);Vincent et al., 2022), it is high-flow events that tend to drastically rework fan morphology by reshaping or redirecting channels, often with catastrophic consequences for people or infrastructure on those fans (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Numerous experimentalists have adapted the method to the remote sensing of model topography, most commonly with convergent cameras mounted on a rolling instrument cart above the experiment. Laboratory ‘SfM’ has been used to monitor experiments with braided rivers (Javernick et al., 2018; Kasprak et al., 2015; Leduc et al., 2019; Middleton et al., 2019; Peirce et al., 2018, 2019), alluvial fans and steep unconfined flows (Leenman & Eaton, 2021; Leenman et al., 2022; Piton et al., 2018; Vincent et al., 2022), estuaries (Braat et al 20192019; Leuven et al., 2018), step‐pool channels (Wang et al., 2021; Zhang et al., 2020), Martian valley evolution (Marra et al., 2014), bridge scour (Ramos et al., 2016), bedforms (Adams & Zampiron, 2020; Bankert & Nelson, 2018; Nelson & Morgan, 2018; Polvi, 2021), alluvial cover (Buechel et al., 2022;Papangelakis et al., 2021; Welber et al., 2020), and the effects of plants and wood (Spreitzer et al., 2020b, 2021; Wang et al., 2016).…”
Section: Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experimentalists have adapted the method to the remote sensing of model topography, most commonly with convergent cameras mounted on a rolling instrument cart above the experiment. Laboratory ‘SfM’ has been used to monitor experiments with braided rivers (Javernick et al., 2018; Kasprak et al., 2015; Leduc et al., 2019; Middleton et al., 2019; Peirce et al., 2018, 2019), alluvial fans and steep unconfined flows (Leenman & Eaton, 2021; Leenman et al., 2022; Piton et al., 2018; Vincent et al., 2022), estuaries (Braat et al 20192019; Leuven et al., 2018), step‐pool channels (Wang et al., 2021; Zhang et al., 2020), Martian valley evolution (Marra et al., 2014), bridge scour (Ramos et al., 2016), bedforms (Adams & Zampiron, 2020; Bankert & Nelson, 2018; Nelson & Morgan, 2018; Polvi, 2021), alluvial cover (Buechel et al., 2022;Papangelakis et al., 2021; Welber et al., 2020), and the effects of plants and wood (Spreitzer et al., 2020b, 2021; Wang et al., 2016).…”
Section: Topographymentioning
confidence: 99%
“…Through‐water photogrammetry is ideally suited to the laboratory ‘environment’, given the typically shallow flow depths and the clear flow that results from the removal of fine grains to avoid non‐scaled cohesion and hydraulically smooth experimental channel beds. Moreover, the small size of many laboratory models allows for synchronous camera arrays that enable instantaneous topographic surveys without stopping the experiment (e.g., Leenman & Eaton, 2021; Leenman et al., 2022; Vincent et al., 2022). The technique therefore allows continuous topographic monitoring, which has so far been applied only to the planform (two‐dimensional) evolution of experimental and field‐scale rivers through the use of time‐lapse imagery.…”
Section: Topographymentioning
confidence: 99%
“…Their experiments showed that changing the flood intermittency altered the timing of the equilibrium state, with low intermittency systems being in a constant state of adjustment between erosional and depositional systems. Leenman et al (2022) found that for variable discharge experiments, the shape of the flood hydrograph has important impacts on both lateral channel migration and overall morphologic change.…”
mentioning
confidence: 99%
“…Physical models have long been used in alluvial fan research, with experimental studies taking place as early as the 1960s (Hooke, 1967(Hooke, , 1968. Recently there have been a number of experimental studies of alluvial fan processes and forms (Clarke et al, 2010;Eaton et al, 2017;Hamilton et al, 2013;Leenman & Eaton, 2021;Leenman et al, 2022). While many of these studies focus on fluvial processes, recent work by de Haas et al (2015de Haas et al ( , 2016de Haas, Densmore, Stoffel, et al, 2018) has centered on debris flow fan formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation